IMPLEMENTASI LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS AUGMENTED REALITY (AR) UNTUK MENGOPTIMALKAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP DI PINANGSORI - andre kristian siallagan; Roslian Lubis; Muhammad Syahril Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
This study aims to implement an Augmented Reality-based Student Worksheet (LKPD) on the topic of three-dimensional shapes with flat surfaces to optimize the mathematical conceptual understanding of junior high school students in Pinangsori. The study uses the Plomp development model, which consists of five phases: initial investigation, design, realization, testing-evaluation-revision, and implementation. The instrument used is a test sheet measuring students' mathematical conceptual understanding. The research subjects consist of 29 students. Effectiveness is determined based on students' test scores. The analysis results show that the Augmented Reality-based LKPD (BASTAR) for the topic of three-dimensional shapes with flat surfaces has an effectiveness of 96%>85% of students achieving mastery with effective criteria. The conclusion of the study is that the implementation of the Augmented Reality-based LKPD (BASTAR) is considered effective for teaching three-dimensional shapes with flat surfaces to junior high school students.